Acquisition and Development of Verb/Predicate Chaining in Hebrew - Berman, Ruth; Lustigman, Lyle (Frontiers in Psychology, 2020)
The study considers development and use of verb/predicate chaining constructions by Hebrew speakers from early childhood to adolescence, based on analysis of authentic conversational and narrative corpora. Three types of such constructions are considered, ordered hierarchically by stage of acquisition: (1) monoclausal extended predicates consisting of a verb (modal, aspectual, or evaluative) marked for tense or mood and followed by one or more complements in the infinitive – e.g., yaxol la-asot ‘can, is able to-do’; (2) coreferential interclausal predicate chaining; and (3) mature discursively-motivated topic-chaining. Relevant typological features of Modern Hebrew are reviewed to explain the lack of canonic clause-chaining construction in the language (e.g. the paucity of non-finite constructions in everyday usage, lack of an uninflected basic form of verbs, lack of auxiliary verbs expressing categories of aspect and voice, and monolexemic verb-internal complexity). Monoclausal verb-chaining emerges early in the speech of toddlers in interaction with their caretakers, whereas predicate chaining by coordination across clauses occurs only later, and chunking of such constructions at the service of discourse connectivity is a late-developing device. Nonfinite subordination is an advanced form of clause-combining, in contrast to straightforward subordination with the multifunctional subordinator še’that’. The conclusion is that, unlike the obligatorily fused monoclausal “extended predicates”, bi- and multi-clausal predicate chaining represents an optional rhetorical choice on the part of a given speaker-writer in a particular communicative context.